A plant design on bunker fuel oil from bamboo cellulose - Calachan, Ayrin T. (College of Engineering, 1982)
Plant capacity: 62.116 tons oil per day -- Plant area: 225,000 sq feet -- Regulated cost: P 5164874.72 -- Total purchased equipment cost: P 61965201.00 -- Direct plant cost: P 123873022.00 -- Indirect plant cost: P 34684446.16 -- Total plant cost (D/I): P 158557468.10 -- Fixed capital investment: P 182341088.30 -- Total capital investment: P 364682176.60 -- Variable cost: P 102589237.50 -- Break-even point: none -- Sales: P 112249444.50